2016
DOI: 10.1080/02626667.2015.1019507
|View full text |Cite
|
Sign up to set email alerts
|

Testing new sources of topographic data for flood propagation modelling under structural, parameter and observation uncertainty

Abstract: This study assessed the utility of EUDEM, a recently released digital elevation model, to support flood inundation modelling. To this end, a comparison with other topographic data sources was performed (i.e. LIDAR, light detection and ranging; SRTM, Shuttle Radar Topographic Mission) on a 98-km reach of the River Po, between Cremona and Borgoforte (Italy). This comparison was implemented using different model structures while explicitly accounting for uncertainty in model parameters and upstream boundary condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This study employs the EU-DEM 23 , which is largely SRTM based and would thus be expected to provide similar accuracy. A first study comparing SRTM and EU-DEM products for flood modeling did not find significant differences 15 . However, since all elevation data were averaged to the same resolution as SRTM, the benefit of the higher resolution of the EU-DEM was not assessed.…”
Section: Technical Validationmentioning
confidence: 98%
“…This study employs the EU-DEM 23 , which is largely SRTM based and would thus be expected to provide similar accuracy. A first study comparing SRTM and EU-DEM products for flood modeling did not find significant differences 15 . However, since all elevation data were averaged to the same resolution as SRTM, the benefit of the higher resolution of the EU-DEM was not assessed.…”
Section: Technical Validationmentioning
confidence: 98%
“…Neal et al (2012b) demonstrated that simpler models might achieve similar accuracies to more complex model in some circumstances. In a model conditioning and evaluation context, simpler models with coarse-resolution low-accuracy topographic data might even over perform that based on high-resolution high-accuracy ones (Mukolwe et al, 2015). Those examples illustrate that simply bringing in more detailed data neither cannot solve the issue of equifinality nor improve the model performance.…”
Section: Equifinality and Data-model Relationmentioning
confidence: 99%
“…Tyralla and Schumann (2016) present a new approach for dealing with model structural uncertainty. Mylopoulos and Sidiropoulos (2016) consider the management of an aquifer under uncertain hydrogeology of the subsurface and propose a stochastic optimization approach, while Mukolwe et al (2016) deal with uncertainties on the surface, studying the influence of various elevation datasets on accuracy of flooding models. Kabeya et al (2016) quantify the effects of forest harvesting versus climate on streamflow variability and trend, while Koga et al (2016) present an urban-scale hydrological application accounting for the uncertainty in land-use delineation.…”
Section: Preface-special Issue: Facets Of Uncertaintymentioning
confidence: 99%